A tuned Lewis acidic catalyst guided by hard–soft acid–base theory to promote N2 electroreduction. Issue 22 (25th May 2021) - Ren, Yongwen; Yu, Chang; Song, Xuedan; Zhou, Fengyi; Tan, Xinyi; Ding, Yiwang; Wei, Qianbing; Hong, Jiafu; Qiu, Jieshan
Abstract : A paradigm of catalyst design for enhancing N2 activation is presented based on hard–soft acid–base theory using a MoS x model catalyst. The optimized MoS x delivers a NRR Faradaic efficiency of 21.60 % and NH3 yield rate of 40.4 μg h –1 mgcat. –1 . Abstract : The electrocatalytic N2 reduction reaction (NRR) to ammonia (NH3 ) driven by intermittent renewable electricity under ambient conditions offers an alternative to the energy-intensive Haber–Bosch process. However, as a distinct core of the process, the design strategy of the electrocatalyst for enhancing the N2 activation ability is still in a trial-and-error stage due to the absence of theoretical guidance. As a result, the corresponding NH3 yield rate and selectivity are much lower than that required for implementation at scale. In this work, on the basis of the hard–soft acid–base theory, we report a paradigm for the design of an electrocatalyst with tuned Lewis acidity to efficiently activate and reduce N2 to NH3 . As a proof of concept, it is revealed that enhancing the Lewis acidity of the molybdenum sulfide (MoS x ) model catalyst supported on carbon nanotubes can greatly improve its activation ability toward the N2 molecule. Accordingly, a high faradaic efficiency of 21.60 ± 2.35% and NH3 yield rate of 40.4 ± 3.6 μg h −1 mgcat. −1 are obtained over the modified MoS x, which are ∼2 times enhanced in comparison with the original MoS x, respectively. Density functional theory calculations verify that the electron transfer from the occupied σ orbitals of N2 to the empty d orbitals of Mo sites within MoS x can be greatly accelerated by tuning the Lewis acidity of MoS x to match with the basicity of N2, thereby enhancing the N2 activation process via the σ → d donation mechanism.